HOW CAN SOCIAL MEDIA REVOLUTIONIZE INFORMAL ENGLISH LEARNING? UNVEILING LEARNING GOALS, ADVANTAGES, AND DISADVANTAGES - Kusuma, I Putu Indra; Wahyuni, Luh Gede Eka; Roni, Marianus; Hashim, Haida Umiera (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Previous studies have revealed that social media (SM) was implemented in EFL (hereafter, EFL) students’ online informal learning of English (OILE). However, the information about learning goals, pros, and cons of doing these activities remains unclear. Thus, this study aimed to explore (1) the learning goals of online informal learning of English via SM and (2) the students' perceptions of the advantages and disadvantages of using SM to facilitate OILE. This basic qualitative study recruited 14 EFL students at a university in Indonesia to join in semi-structured interviews. The interview results were analyzed using inductive thematic analysis. The findings revealed that EFL students engaged in OILE via SM for various goals (mostly for form-focused and meaning-focused goals), focusing on learning and practicing language skills. However, those learning goals primarily focused on form than meaning. In addition, the participants confessed that doing OILE brought advantages to cognitive and affective domains. Unfortunately, the participants also perceived that doing such OILE also brought some disadvantages. From the findings, we offered some implications to advance EFL learning through OILE via SM.